Energy Transition in Colombia: An Implementation Proposal for SMEs (2024)
The environmental summits in Rio de Janeiro, Kyoto, Johannesburg, Bali, Copenhagen, and Paris significantly contributed to raising awareness among nations about the need to reduce greenhouse gas (GHG) emissions. In this context, the energy transition from carbon-based energy sources to renewable energy sources is one of the main goals for both states and companies in the short and medium term. Therefore, the objective of this article is to propose a methodological route for the implementation of energy transition in Colombian SMEs. To achieve this objective, it was necessary to analyze the climate change and energy transition programs included in Colombia’s development plans. The results show that SMEs do not have significant participation in energy transition processes, mainly due to the economic and market barriers they face. However, the fiscal incentives and subsidies established by the government since 2018 increase opportunities for their participation in the present and the coming years.